SAT0050 IL4-10 Synerkine Induces Direct and Indirect Structural Cartilage Repair in OA. (9th June 2015) - Pustjens, M.F.; Steen-Louws, C.; van Roon, J.A.; Hack, C.E.; Mastbergen, S.C.; Lafeber, F.P.
Abstract : Background: Cartilage damage and inflammation are clear characteristics of joint degeneration in OA. In human and animal in vivo and in vitro experimental models, the immunoregulatory cytokines IL-4 and IL-10, both individually or combined, were shown to be effective in joint degeneration [1]. The additive effects of the cytokines are of importance to achieve this effect. We recently developed IL4-10 synerkine, a fusion protein composed of IL-4 and IL-10, with preserved activities of the individual cytokines. Objectives: This study evaluates the cartilage protective and anti-inflammatroy effects of IL4-10 synerkine ex vivo . Methods: OA cartilage (n=7, age 60 years) was cultured for 4 days in presence or absence of IL-4 (10ng/ml), IL-10 (10ng/ml), a combination of IL-4 (10ng/ml) and IL-10 (10ng/ml), or IL4-10 synerkine (20ng/ml). Changes in proteoglycan (PG) synthesis and PG release were studied. OA synovial tissue (n=8, age 66 years) was cultured for 3 days under similar circumstances. Cytokine levels in culture medium supernatants of both cartilage and synovium cultures were measured by ELISA for IL-6, IL-8 and TNFα. In addition, conditioned medium of synovial tissue cultures (n=3, age 61 years) cultured in presence or absence of IL4-10 was tested on healthy cartilage (changes in PG synthesis and release) to demonstrate indirect synovial effects on cartilage. Results: Culturing OA cartilage in presence of IL4-10 synerkine increased proteoglycan (PG) synthesis with 47.6% (p=0.018), +26.6% for IL-4 alone, +31.2% for IL-10 alone, or +6.9% for IL-4 and IL-10 combined. In addition, a reduction of -8.7% (p=0.018) in PG release was found for IL4-10 synerkine (-4.9% for IL-4 alone, -8.6% for IL-10 alone, or -6.7% for IL-4 and IL-10 combined). The overall improved proteoglycan turnover was in cocurrence with a significant inhibition of Il-6, IL-8 and TNF-α cytokine production by the cartilage in presence of the IL4-10 synerkine (IL-6 -81.9%, IL-8 -65.9% and -2.0% TNF-α, resp.). Moreover, IL4-10 synerkine also reduced the production of IL-6, IL-8 and TNFα in osteoarthritic synovium (-83.5%, -85.6% and -25.9% resp., all p<0.01). When conditioned culture medium of synovial tissue was tested on healthy cartilage, a changed PG turnover was seen (-77% PG synthese, +21%, PG release). This PG turnover was normalized to healthy levels by IL4-10 treated synovium. There was no direct effect of IL4-10 synerkine on healthy cartilage. Conclusions: These data show that IL4-10 synerkine induces both structural repair and reduce inflammation in OA. Ex vivo, IL4-10 synerkine has a direct effect on OA cartilage by affecting its proteoglycan turnover and cytokine production. Inhibiting the synovial cytokine production, adds indirectly to this structural repair of the cartilage. Together with the pain inhibiting effects found in animal models of OA, these data suggest disease modifying characteristics of the IL4-10 synerkine. References: Van Roon JA, Lafeber FP, Bijlsma JW. (2001). Synergistic activity of interleukin-4 and interleukin-10 in suppression of inflammation and joint destruction in rheumatoid arthritis. Arthritis & Rheumatism 44(1): 3-12. Disclosure of Interest: M. Pustjens: None declared, C. Steen-Louws: None declared, J. van Roon: None declared, C. Hack Shareholder of: Executive scientific director Prothix, S. Mastbergen: None declared, F. Lafeber: None declared